Energy storage and conversion materials - Skinner, Stephen (Inorganic materials series (Royal Society of Chemistry (Great Britain)) ;, 2020)
Showcasing recent developments in inorganic materials in an area of societal interest and importance, this book provides an up-to-date introduction to the contemporary use of functional solids in emerging technologies. Energy Storage and Conversion Materials describes the application of inorganic materials in the storage and conversion of energy, with an emphasis on how solid-state chemistry allows development of new functional solids for energy applications. Dedicated chapters cover co-electrolysis, low temperature fuel cells, oxide thermoelectric devices for energy conversion, solid-state Li batteries and thermochemical energy conversion. Edited and written by world-renowned scientists, this book will provide a comprehensive introduction for advanced undergraduates, postgraduates and researchers wishing to learn about the topic.